Hepatic Injury in Poisoning Cases: An Autopsy Study - Khadilkar, Niranjan P; Nagesh, K R; Rai, Preethi; Varghese, Annie; Surana , Nikita (Journal of Indian Academy of Forensic Medicine, 2016)
Poisons act on various organs in the body that may result in fatality. In the present study, the liver pathology in various poisoning cases was studied in autopsied bodies that were conducted in a tertiary care hospital in Mangalore. The incidence of poisoning was equal in third, fourth and fifth decades with male to female ratio 7:3. The predominant poison responsible for fatality was Organophosphorus compound followed by Pyrethyroid, zinc sulphide and Carbamates. Majority of the victims survived for less than 6 hours. Serum bilirubin level was raised in organophosphate, Pyrethyroid and zinc phosphide poisoning. Serum liver enzyme levels were raised in zinc phosphide, copper sulphate, Pyrethyroid and organophosphate poisoning. Congestion was the predominant gross finding seen in all the poisoning cases. Yellowish discoloration of liver was mainly seen in paraquat, zinc phosphide and organophosphate poisoning. The predominant microscopic finding was congestion, steatosis, periportal lymphocytic infiltration, intrahepatic haemorrhage, centrilobular necrosis and intrahepatic cholestasis.